Analisis Miskonsepsi Siswa SD pada Topik Gerak - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a systematic literature review (SLR) adapted from the PRISMA method to identify and analyze the types and prevalence of misconceptions among elementary school students on motion topics. The main goal is to present a comprehensive profile of misconceptions from national empirical studies to support science education interventions at the elementary level. Article subjects include 20 primary studies from SINTA 1-6 journals and other sources (2020-2026), involving 729 elementary school/MI students in 4th - 6th grades from various Indonesian regions. Data collection used systematic searches in Sinta, Garuda, and Google Scholar databases with specific keywords ("elementary student motion misconceptions", etc.), yielding 7,280 initial articles filtered by inclusion criteria (CRI/2-4 tier diagnostic tests, sample ≥15 elementary students) and exclusion criteria (non-elementary, grey literature). Data analysis employed quantitative descriptive methods: topic classification (gravity, friction, general force, inertia, resultant), average misconception prevalence calculation per subtopic, and triangulation of causal factors. Results show overall misconception prevalence of 62.15%, highest in gravity (82.63%: "Earth pushes down"), friction (78.38%: "friction always stops"), followed by general force (61.78%), resultant (60.83%), and inertia (67%). Dominant factors: students (44%, Aristotelian/Piaget intuition), ambiguous IPAS textbooks (24%), teacher lectures (24%). Conclusion: confirms resistant misconceptions hinder 80% IPAS competency in grade IV, risking propagation to junior high, recommending BSE revisions, CRI training, and conceptual change for national STEM foundation.